Pengaruh Struktur Modal dan Pertumbuhan Penjualan Terhadap Profitabilitas (Studi Kasus PT. Delta Djakarta Tbk) - Hermanus, Meykel; Silaya, Micrets Agustina; Laisila, Maya (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2022)
This study aims to determine how the influence of capital structure on profitability, sales growth on profitability, as well as capital structure and sales growth on profitability at PT. Delta Jakarta Tbk. This research is an exploratory research, with a quantitative descriptive approach through Debt to Equity Ratio (DER), Sales Growth and Return On Asset (ROA) which is analyzed using multiple linear regression method. The results showed that the partial capital structure had a negative effect on profitability with a significant value of 0.033 while partial sales growth with a significant value of 0.211 had a positive effect on profitability, while these two independent variables, namely capital structure and sales growth, simultaneously had a significant effect and significant on profitability with a significant value of 0.041.